Specific Characteristics of Professional Competence Formation in Future Teachers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the concept of competence, professional competence, competent approach, professionally competent teacher, some work that needs to be done if the formation of professional competence of future teachers is considered as a pedagogical problem, the concept of competence in professional competence and There is a need to pay attention to the forms of theoretical training of future teachers in the formation of professional competence.